Analyses of Ecological Footprint at Bangladesh Agricultural Research Institute (BARI) Residential Area (Journal of Environmental Science and Natural Resources, 2021)
Ecological Footprint (EF) assessment helps to identify what activities are having the biggest impact on nature and opens up possibilities to reduce our impact and live within the means of one planet. The introduction of EF has been very necessary for the context of Bangladesh especially in the industrial areas such Gazipur as the endless demand and the unplanned consumption pattern of the population here have been producing a very unsustainable situation. Thus this study intends to initiate it by calculating the Ecological Footprint of Bangladesh Agricultural Research Institute (BARI), one of the important residential area of Gazipur and major consuming areas of that city as a sustainability indicator. Basic equation for assessing EF has been done according to Nunes et al. (2013). EF has been calculated for these components: energy, food, waste and building material consumption. Questionnaire survey has been conducted to gather information about consumption pattern for different components in the households of BARI residential area. The study also identified consumption of natural gas for household purpose as the most contributing factor in the footprint of BARI residential area followed by waste, building materials and electricity consumption.Environ. Sci. & Natural Resources, 12(1&2): 143-149, 2019